Electric field enhancement in ceramic capacitors due to interface amplitude roughness. Issue 4 (April 2019) - Heath, James P.; Harding, John H.; Sinclair, Derek C.; Dean, Julian S.
Abstract: The electrical behaviour of the interface between the ceramic and electrode layers in multi layer ceramic capacitors has been studied using finite element modelling. Interface models were produced with varying amplitudes of roughness based upon analysis of micrographs both captured in-house and from the literature. The impedance responses, direct current electric field and current density distributions of the different interfaces were compared. Increasing the root-mean-squared amplitude roughness from 0 to 0.16 μm increased the maximum field strength by over a factor of four. The electric field distribution showed that fluctuations in the increase of field strength were due to local interface morphology. Sharp intrusions of the electrode into the ceramic layer resulted in particularly large field enhancements and should be avoided to reduce the likelihood of device breakdown.